HYSTOPATHOLOGIC CHANGES ON AORTA OF CIRRHOSIS MALE RATS (RATTUS NORVEGICUS) INDUCTED BY ESCHERICIA COLI O55 : B5 - Hartono, Tony; Misaco Yuniarti, Wiwik; Sektiari Lukiswanto, Bambang (Jurnal Veteriner; Vol 9 No 3 (2008))
The background of this study is to visualize histopathological changes on aorta of cirrhosis rats (Rattus norvegicus) induced by endotoxin E. coli O55 : B5 This study was a laboratory experimental using complete randomized design with five treatments and five repetitions. Twenty five male Wistar rats were used as experimental model of cirrhosis by bile duct ligation (BDL) technique. Three weeks after BDL, all cirrhosis experimental models were induced with a single intra venous injection of Eschericia coli endotoxin (3mg/kg b.b in 1 ml sterile saline), except those of five control rats that induced with sterile saline at the same volume only. Aortas of control rats group were excised at 6 hours after induction with sterile saline, whereas the other four groups were done at 6, 12, 18 and 24 hours after induction with endotoxin. The quantity of endothelial cell, discontinuity increment and the thickness of internal elastic lamina layer were observed to know histopathological changes on aorta. Histopathological changes were observed using a light mycroscope, dyscontinuity and thickness of internal elastic lamina were measured by reticular micrometer. The quantity of endothelial cell on control and observation interval of 6 and 12 hours as significant difference (P<0.05), which are bigger than that of 18 and 24 hours. Rats in the control group have the biggest quantity comparing to the other treatments. Discontinuity and thickness of internal elastic lamina layer had significant difference (P<0.05) on control, observation on 6 and 12 hours compared to observation on 18 and 24 hours after being induced with endotoxine. The highest discontinuity and the thinnest elastic lamina internal were obtained within observation on 24 hours. VCAM-1 expression on control group differ from observation on 6 and 12hours but all of them have significant difference to observation on 18 and 24 hours (P<0,05). The decrease of endothelial cell number is caused by endothelial cell contact with endotoxin. Longer contact interval can make more severe injury and dysfunction. When the aorta had loss of its endothelial cell, internal elastic lamina will exposed with endotoxin directly. In the vessel, endotoxin cause nitric oxide (NO) release, that have antiproliferative characteristic for neointimal formation. This condition presumed to be the cause of the dyscontinuity increment and thickness decrement of internal elastic lamina of cirrhosis rats. VCAM-1 expression was influenced by quantity and condition of endothelial cell. The higher VCAM-1 expression in control group higher than the other group because the quntity and morphofunction of endothelial cell was better than that of 6, 12, 18 and 24 hours.
Keywords: cirrhosis, endotoxin, endothelial cell, discontinuity, thickness, internal elastic lamina